"China, Unaona Mkono Yangu Ama Una-nini?": The Wedding Engagement between Kenya and China in the Churchill Comedy Show. Issue 2 (3rd April 2022) - Yuan, Mingqing; Shen, Yuning
ABSTRACT: Comedy shows are an acute barometer of social contexts as they are embedded in power relations and often constructed as a space of resistance. With the increasing presence of China in Kenya, China has been a recurring theme in one of the most popular Kenyan stand-up comedies, the Churchill Comedy Show . In 2018, a clip circulated widely of a Chinese female comedian on stage with Churchill and Sleepy. In the clip they discuss the debt issue between Kenya and China through romantic metaphors of an "engagement" ceremony before the wedding, including both expressions of love and bargaining about bride price. This article argues that humour and laughter help in carving out a space for open discussions and critical reflections on the debt issue within Kenya–China relations. It inserts agency and expresses resistance and moral critique of Chinese engagements in Kenya, especially from socio-economically marginalised publics. At the same time, the humour jointly generated through a reiteration of tropes of nationhood, separation of languages and gendered expressions runs the risk of taking interpersonal relations back to rigidly divided national, ethnic and gendered categorisations and representations.